UMP garnered 18 medals and a special award at ITEX 2013 - UMP, PNC
Universiti Malaysia Pahang (UMP) won 18 medals and one special award in the International Invention, Innovation and Technology Exhibition 2013 (ITEX ’13) held at Kuala Lumpur Convention Centre (KLCC) from May 9-11, 2013.